PENGEMBANGAN MEDIA PEMBELAJARAN AR BERBANTUAN ASSEMBLR EDU TYPE MERGE CUBE DALAM MATERI IPAS KELAS V - Maysaroh, Luluk; Purnawanto, Ahmad Teguh; Mariyani, Anna (Jurnal Kiprah Pendidikan, 2025)
This research is motivated by the minimal use of interesting and enjoyable learning media, as well as the absence of learning media.ARat SDN 1 Gempolrejo. Learning media is still in printed form, so the display is less attractive and the variations are limited, so students feel bored. This study aims to develop Augmented Reality (AR)-based learning media using the Assemblr Edu platform in the form of a Merge Cube, and to test the feasibility of the resulting product. The media developed is a 3D visual material that can be accessed via QR Code on the sides of the Merge Cube. The method used is Research and Development (R&D) with the ADDIE model (Analisys, Design, Development, Implementation, Evaluation). The subjects of the study were 24 fifth-grade students of SDN 1 Gempolrejo. Data collection techniques included interviews, questionnaires, and documentation; data were analyzed qualitatively and quantitatively from 3 media validators, namely design experts, material experts, and language experts as well as the results of small group student trials, large group trials, and from fifth-grade teachers. The validation results showed that the media was very suitable for use, with an assessment from design experts of 97%, material experts 80%, and language experts 94%. Student responses showed high interest (91%) and teachers rated the media as very interesting (94%). Thus, this media was declared valid, interesting, and suitable for use as a reference for science learning, especially natural disaster material.